ANALISIS KOMPETENSI GURU, TANTANGAN PEDAGOGIK, DAN STRATEGI PENINGKATAN KOMPETENSI GURU - Endah Windarti; Yuliana Nur Amini; Indarwati Indarwati; Joni Tri Wahyono; Arief Rahman Yusuf (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the implementation of bilingual education at Semesta Bilingual Boarding School Semarang, focusing on teacher competence, pedagogical challenges faced, and improvement strategies applied. The research method used was a qualitative approach through direct observation and semi-structured interviews with the principal and teachers. The results of the study show that the implementation of bilingual education in this school has been running well and is supported by modern infrastructure such as interactive boards and Chromebooks. Teachers demonstrate strong professional and pedagogical competencies, although there are still variations in English proficiency and the application of Content and Language Integrated Learning (CLIL). The main challenges include the uneven linguistic abilities of teachers, the adaptation of new students to the bilingual system, and the suboptimal use of technology. Improvement efforts are carried out through regular training, workshops, seminars, and strengthening the teacher performance monitoring or evaluation system. This study concludes that the success of bilingual education is not only determined by language skills, but also by a continuous teacher professional development system, institutional support, and contextual instructional design. ABSTRAK Penelitian ini bertujuan untuk menganalisis implementasi pendidikan bilingual di Semesta Bilingual Boarding School Semarang, dengan fokus pada kompetensi guru, tantangan pedagogik yang dihadapi, serta strategi peningkatan yang diterapkan. Metode penelitian yang digunakan adalah pendekatan kualitatif melalui observasi langsung dan wawancara semi-terstruktur dengan kepala sekolah dan guru. Hasil penelitian menunjukkan bahwa implementasi pendidikan bilingual di sekolah ini telah berjalan dengan baik dan ditunjang oleh infrastruktur modern seperti interactive board dan Chromebook. Guru menunjukkan kompetensi profesional dan pedagogik yang kuat, meskipun masih terdapat variasi dalam penguasaan bahasa Inggris dan penerapan pembelajaran berbasis Content and Language Integrated Learning (CLIL). Tantangan utama meliputi ketidakmerataan kemampuan linguistik guru, adaptasi siswa baru terhadap sistem bilingual, serta pemanfaatan teknologi yang belum optimal. Upaya peningkatan dilakukan melalui pelatihan rutin, workshop, seminar, penguatan sistem monitoring atau evaluasi kinerja guru. Penelitian ini menyimpulkan bahwa keberhasilan pendidikan bilingual tidak hanya ditentukan oleh kemampuan bahasa, tetapi juga oleh sistem pengembangan profesional guru yang berkelanjutan, dukungan kelembagaan, dan desain instruksional yang kontekstual.